Endothelial interferon regulatory factor 1 cooperates with NF-kappa B as a transcriptional activator of vascular cell adhesion molecule 1. - Neish, A S (1995)
Transcription of the vascular cell adhesion molecule 1 (VCAM-1) gene in endothelial cells is induced by lipopolysaccharide and the inflammatory cytokines interleukin-1 beta and tumor necrosis factor alpha (TNF-alpha). Previous studies have demonstrated that tandem binding sites for the inducible transcription factor NF-kappa B are necessary but not sufficient for full cytokine-mediated transcriptional activation. Herein, we demonstrate that full cytokine-induced accumulation of VCAM1 transcript requires protein synthesis. We report the definition of a functional regulatory element in the VCAM1 promoter interacting with the transcriptional activator interferon regulatory factor 1 (IRF-1). DNA-protein binding studies with endothelial nuclear extracts revealed that IRF-1 is cytokine inducible and binds specifically to a consensus sequence motif located 3' of the TATA element. We have identified heterodimeric p65 and p50 as the NF-kappa B species binding to the VCAM1 promoter in TNF-alpha-activated endothelial cells. Experiments with recombinant proteins showed that p50/p65 and high-mobility-group I(Y) protein cooperatively facilitated the binding of IRF-1 to the VCAM1 IRF binding site and that IRF-1 physically interacted with p50 and with high-mobility-group I(Y) protein. Transient transfection assay in endothelial cells showed that overexpressed IRF-1 resulted in superinduction of TNF-alpha-stimulated transcription. Site-directed mutations in the IRF binding element decreased TNF-alpha-induced activity and totally abolished superinduction. Cotransfection assays in P19 embryonal carcinoma cells revealed that IRF-1 synergized with p50/p65 NF-kappa B to activate the VCAM1 promoter or heterologous promoter constructs bearing isolated VCAM1 NF-kappa B and IRF binding motifs. Cytokine inducibility of VCAM1 in endothelial cells utilizes the interaction of heterodimeric p50/p65 proteins with IRF-1.